Movement, home range size and activity pattern of the golden jackal (Canis aureus, Linneaus, 1758) in Huai Kha Khaeng Wildlife Sanctuary, Thailand - Khwanrutai Charaspet; ronglarp - sukmasuang; Noraset Khoewsree; Mananya Pla-ard; Nucharin Songsasen; Saksit Simchareon (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Charaspet K, Sukmasuang R, Khoewsree N, Pla-ard M, Songsaen N, Simchareon S. 2019. Movement, home range size and activity pattern of the golden jackal (Canis aureus, Linneaus, 1758) in Huai Kha Khaeng Wildlife Sanctuary, Thailand. Biodiversitas 20: 3430-3438. We studied the movement patterns, monthly home range sizes, and activity patterns of the golden jackal in Huai Kha Khaeng Wildlife Sanctuary (HKK) from November 2017 to June 2019. Data were obtained by trapping and collaring a female jackal with a satellite collar, and from a concurrent camera trap survey. The female jackal had an average daily movement of 1.7 km, and her overall home range size was 26.3 km2, based on 1,191 locations across 7 months and using the 95% Minimum Convex Polygon (MCP) method. The monthly home range size (95% MCP) was the smallest in December (9.2 km2) and the largest in March (20.51 km2). Results from camera traps revealed 33 species of wild animals, including 16 species of carnivorous mammals and 17 non-carnivorous species. The relative abundance index (RAI) of the jackal was 24.33, which was the highest of all carnivore species, and the second-highest of all species, suggesting jackals were one of the most common mammal species in HKK. Based on camera trap data, the mean diel activity of jackals in HKKwas at 00: 46 hours, and their activity overlapped most with potential prey including hares and small rodents. Results also revealed that golden jackals prefer dry dipterocarp forest compared to other habitat types Our results lead to a better understanding of the ecology of golden jackals in Thailand, and provide a baseline for future research on this species.